Presence of the endangered saproxylic species Cucujus haematodes (Coleoptera: Cucujidae) in Aspromonte National Park (Southern Italy). Issue 1 (31st December 2022) - Bonacci, T.; Biscaccianti, A. B.; Siclari, A.; Carlomagno, F.; Bonelli, D.; Mendicino, F.; Plewa, R.; Jaworski, T.; Pezzi, M.
Abstract: The knowledge of the ecological preferences of threatened species is critical to all conservation programs. Analyses of habitats and ecological parameters of species are necessary to predict future distribution and responses to climate change. Cucujus haematodes Erichson, 1845 (Coleoptera: Cucujidae) is a threatened obligate saproxylic species, listed in the IUCN European Red List of Saproxylic Beetles. After a few decades of apparent absence, the species was recently found in Calabria (Southern Italy) in some good quality biotopes of the Sila National Park in association with Cucujus cinnaberinus (Scopoli, 1763) and Cucujus tulliae Bonacci, Mazzei, Horák & Brandmayr, 2012 (Coleoptera: Cucujidae). Field surveys carried out from 2014 to 2020 in Aspromonte National Park (Calabria) revealed large populations of C. haematodes . Larvae of C. haematodes were collected from under the bark of dead trees in 11 sampling areas within Aspromonte National Park. The presence of larvae of C. haematodes on the non-autochthonous conifer Pseudotsuga menziesii (Mirb.) Franco (Pinales: Pinaceae) was also reported for the first time in Italy.